Does bone wax make sense in off-pump coronary surgery? A prospective randomized study - Sorm, Zdenek; Vobornik, Martin; Děrgel, Martin; Cermakova, Eva; Harrer, Jan; Gofus, Jan (Kardiochirurgia i Torakochirurgia Polska, 2023)
INTRODUCTION: The effect of bone wax on sternal infection and intraoperative bleeding in off-pump coronary surgery has not been reported in current literature. AIM: To prospectively evalute this in a cohort of high risk patients undergoing off-pump coronary artery surgery at our institution. The potential impact on cell saver utilization was also studied. MATERIAL AND METHODS: A prospective randomized study was performed in 58 diabetic patients operated on for two-vessel coronary artery disease by the off-pump technique. They were randomly assigned to the wax or no-wax group. RESULTS: There was no significant difference in intraoperative blood loss between the wax (550 ml) and no-wax group (750 ml; p = 0.0711). In multivariate analysis the absence (non-use) of bone wax (odds ratio = 3.9 (1.12-13.51), p = 0.027) and preoperative creatinin level (odds ratio = 1.1 (0.99-1.03), p = 0.03) were identified as independent predictors of blood loss ≥ 750 ml. The number of red blood cell units during hospital stay was similar in both groups (p = 0.42). Wound healing complications were not observed in either group. CONCLUSIONS: The use of bone wax does not lead to a higher risk of sternal wound infection. It may reduce the risk of high intraoperative blood loss, thus avoiding the need of a cell saver during off-pump coronary surgery. However, this influence remains questionable.